The Little Data Book 2008 - World Bank (Washington, DC, 2013)
The little data book 2008 is a pocket edition of World development indicators (WDI) 2008. It is intended as a quick reference for users of the World development indicators 2008 book and CD-ROM and WDI online, and the World Bank electronic subscription database. Together, they cover more than 800 indicators and span more than 40 years. The 209 country tables in the little data book present the latest available data for World Bank member countries and other economies with populations of more than 30000. The 14 summary tables cover regional and income group aggregates.